The Combined Effect of Lighting and Zinc on the Nutritional Quality of Lettuce (Lactuca sativa L.) Grown in Hydroponics - Kristina Laužikė; Rūta Sutulienė; Viktorija Vaštakaitė-Kairienė; Aušra Brazaitytė (Horticulturae)
The nutritional quality and biochemical properties of ‘Little Gem’ (Lactuca sativa L.) lettuce grown hydroponically can be enhanced by Zn and white light. This study investigated the combined effects of wide-spectrum white LED lighting parameters and Zn doses on the Zn accumulation, enzymatic and non-enzymatic antioxidants, sugars, and protein content of lettuce. Broad-spectrum 3500 K light combined with a 5 ppm Zn solution led to a 7% increase in Zn accumulation in lettuce, compared to 3000 K and 4000 K lighting conditions. The 5 ppm Zn dose combined with 3000 K and 4000 K lighting affected DPPH and ABTS scavenging activity and Fe-reducing antioxidant power. Additionally, this combination influenced chlorophyll b, maltose, superoxide dismutase, and ascorbate peroxidase levels. Furthermore, the 1 and 5 ppm Zn doses at 4000 K impacted carotenoids such as neoxanthin, lutein, zeaxanthin, and total protein content. In lettuce exposed to a 1 ppm Zn dose combined with 3000 K and 3500 K lighting, impact was found on total phenolic compounds, sucrose, chlorophyll a, raffinose, fructose, glucose, carotene, violaxanthin, and xanthophylls. The study suggests that lighting and Zn concentrations significantly impact lettuce growth, biochemical properties, and nutritional quality, particularly at the baby leaf stage.